speed control of doubly-fed induction machine using a fuzzy PD+I controller - Mokhtari Mohamed (University of Msila, 2025)
This work presents a fuzzy PD+I control strategy for the speed control of a Doubly-Fed Induction Machine (DFIM). The controller combines the fast response of a PD structure with the steady-state precision of an integral action, enhanced by fuzzy logic adaptation. Simulation results in MATLAB/Simulink show improved speed tracking, reduced overshoot, and better robustness compared to the conventional PI controller.
Keywords: DFIM; Fuzzy PD+I; Fuzzy Logic; Speed Control; Vector Control